Primary Hyperparathyroidism due to Parathyroid Adenoma Originated from Supernumerary Gland - Fernando Mendoza-Moreno; Ángel Rodriguez-Pascual; María Rocío Díez-Gago; Marina Pérez-González; Laura Jiménez‐Alvárez; Isabel Furtado-Lobo; Manuel Díez‐Alonso; Fernando Noguerales-Fraguas (Case Reports in Otolaryngology)
Introduction. The variability of the location of the parathyroid glands is directly related to the events that occur during embryonic development. The impact that an individual submits more than four parathyroid glands is close to 13%. However the presentation of a parathyroid adenoma in a supernumerary gland is an uncommon event. Case report. A 30-year-old man diagnosed with primary hyperparathyroidism with matching findings on ultrasonography and scintigraphy for parathyroid adenoma localization lower left regarding the thyroid gland. A cervicotomy explorer showed four orthotopic parathyroid glands. The biopsy of the inferior left gland was normal. No signs of adenoma were seen in the biopsy. Following mobilization of the ipsilateral thyroid lobe, fifth parathyroid gland was found increased significantly in size than proceeded to remove, confirming the diagnosis of adenoma. After the excision, the levels of serum calcium and parathyroid hormone were normalized. Conclusions. The presentation of a parathyroid adenoma in a supernumerary gland is a challenge for the surgeon. The high sensitivity having different imaging techniques has been a key to locate preoperatively the pathological parathyroid gland. Analytical or clinical persistence of primary hyperparathyroidism after parathyroid surgery can occur if the location of the adenoma is a supernumerary or ectopic gland location.